Eliminating surface transverse cracks in the novel vertical bending continuous casting of pure aluminum 1070 thin slabs - Qijia Mao; Fuan Hua; Zhuohuang Wu; Yuxiao Fu; Guanglin Jia; Guo Yuan; Guodong Wang (Scientific Reports)
Abstract To achieve high-efficiency continuous production of aluminum, vertical bending continuous casting equipment has been designed. However, the formation of surface transverse cracks during casting presents a significant challenge, particularly when producing thin slabs of pure aluminum 1070. This study investigates the high-temperature tensile properties of pure aluminum 1070 thin slabs and conducts numerical simulations of the temperature and stress fields in the vertical bending continuous casting process. The results indicate that a thick solidified shell at the mold outlet, combined with sufficient high-temperature strength and plasticity at the center of the wide surface (1170 mm from the arc section inlet), is essential for resisting thermal and mechanical stresses, thus preventing the formation of surface transverse cracks. The solidified shell thickness at the mold outlet is optimized to no less than 10.8 mm. Additionally, the temperature at the center of the wide surface at an arc length of 1170 mm from the inlet of the arc section and at the outlet of the arc section are effectively controlled to a maximum of 414.0 °C and 365.1 °C, respectively. These adjustments effectively prevent surface transverse cracks in the produced pure aluminum 1070 thin slabs. The novelty of this work lies in the precise regulation of both the temperature and stress fields, offering a solution to the surface crack issue. This study makes significant contributions to optimizing casting parameters for the novel process and enhancing the overall efficiency of aluminum alloy production.